Effect of Treatment With Chitosan, Citric Acid and Malic Acid on Storage of Valencia Orange Fruits - Mohammed, Ahmed Adnan; Kamil, Omar Thaer; Jalil, Omar Turhan (American Journal of Botany and Bioengineering, 2026)
The present investigation was carried out on season 2023 on Valencia orange fruit. The effect of postharvest treatments i.e. chitosan at 2%, citric acid 0.5% and malic acid 150 ppm as well as their combinations on some fruit quality parameters during cold storage at 5°C. 90-95% relative humidity, to assess the effect of treatments on Vitamin C (mg/100g), Juice weight (%), Fruit weight (%), Total sugars (mg/g), Fruit size (cm3) and Total Phenols (mg/100g FW). It was concluded from the results, that Valencia orange fruits treated with chitosan 2% + citric acid 0.5% + malic acid 150 ppm gave the best results during cold storage at 5°C after 90 days.